Passion among breast cancer survivors: A 12-month prospective study. (June 2021) - Schellenberg, Benjamin JI; Sabiston, Catherine M; Vallerand, Robert J; Gaudreau, Patrick
We examined the prospective relationship between harmonious passion and post-treatment health outcomes among female breast cancer survivors. Participants reported passion toward a favorite activity, physical pain symptoms, and mental health after their final breast cancer treatment (Time 1, N = 188). Twelve months later (Time 2, N = 148), participants reported their physical pain symptoms and mental health. Harmonious passion at Time 1 predicted fewer physical pain symptoms and higher levels of mental health at Time 2. These results show that breast cancer survivors benefit from being harmoniously passionate toward a meaningful activity following treatment.